Топос душі в поезії Болеслава Лесьмяна (1877-1937) - Нахлік, Я. (Літературознавчі обрії. Праці молодих учених, 2010)
The research is devoted to the soul topos in the poetry of Young Poland poet Bolesław Lesmian. The aim of the study is to show characteristic features of this topos and to reveal the use of this concept in the epoch of Young Poland. The main features of the soul topos in Lesmian’s poetry are its transcendent origin, connection to corporalness, death, individuality, permanent motion.